1993
DOI: 10.1183/09031936.93.06020237
|View full text |Cite
|
Sign up to set email alerts
|

The large lungs of elite swimmers: an increased alveolar number?

Abstract: In order to obtain further insight into the mechanisms relating to the large lung volumes of swimmers, tests of mechanical lung function, including lung distensibility (K) and elastic recoil, pulmonary diffusion capacity, and respiratory mouth pressures, together with anthropometric data (height, weight, body surface area, chest width, depth and surface area), were compared in eight elite male swimmers, eight elite male long distance athletes and eight control subjects. The differences in training profiles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(21 citation statements)
references
References 47 publications
1
19
1
Order By: Relevance
“…Higher values of forced vital capacity were registered in basketball, water polo and rowers compared to controls. It contrasts with previous reports which found that all athletes, regardless of the sport, had higher lung volumes than physically inactive persons 3,4,6,9,10 . Our study showed that the researched respiratory parameters in athletes had approximately the same value of lung volumes as the control group, except for above mentioned groups.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Higher values of forced vital capacity were registered in basketball, water polo and rowers compared to controls. It contrasts with previous reports which found that all athletes, regardless of the sport, had higher lung volumes than physically inactive persons 3,4,6,9,10 . Our study showed that the researched respiratory parameters in athletes had approximately the same value of lung volumes as the control group, except for above mentioned groups.…”
Section: Discussioncontrasting
confidence: 99%
“…2 Lung volume is fairly well predicted on the basis of age, height and weight, but lung volumes which are larger than predicted have been repeatedly observed in athletes compared to their control counterparts who are not engaged in any kind of regular physical exercise. 3,4 There are some physiological explanations as to why athletes have higher lung volumes, but still, this is an uncharted field. 5 Studies about athletes' respiratory functions are rather limited or have been tested on too small number of participants, mostly related to individual sports.…”
Section: Introductionmentioning
confidence: 99%
“…In 9-10 years old, only inspiratory force (FImax) was significantly higher compared to controls, 29 whereas in older swimmers and runners, forces were not different between the groups. 11 Even if there might be a possible training effect on inspiratory muscle force, the lack of increased inspiratory flows in swimmers weakens the significance of this finding. 28 With the available evidence, the hypothesis that supranormal lung volumes in swimmers directly related to increased respiratory muscle strength and pressures cannot be confirmed.…”
Section: Pathophysiology Of Lung Function Changes In Athletic Swimmersmentioning
confidence: 96%
“…16 Lastly, a study comparing competitive swimmers to long distance runners and non-athletic controls found no difference in P I max and P E max among groups despite the observation that all lung volumes were greater in swimmers. 11 Again, these data go against the assumption that increased lung volumes in swimmers are due to an increased ability to inflate and deflate the lungs in relation to changes in inspiratory/expiratory pressures.…”
Section: Pathophysiology Of Lung Function Changes In Athletic Swimmersmentioning
confidence: 98%
See 1 more Smart Citation